2014
DOI: 10.1074/jbc.m114.586180
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific S-Acylation of Influenza Virus Hemagglutinin

Abstract: Background: S-Acylation of hemagglutinin with stearate and palmitate is essential for influenza virus replication. Results: Mass spectrometry showed that shifting a cysteine from the transmembrane region to a cytoplasmic position eliminates attachment of stearate. Conclusion:The location of the acylation site is the decisive factor for site-specific acylation. Significance: Similar differential acylation might occur in cellular transmembrane proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…For proteins with multiple palmitoylated cysteines, the heterogeneous fatty acylation pattern is different for each cysteine. For example, the hemagglutinin protein (HA) of influenza virus is S-acylated at three cysteines: two contain only palmitate whereas a cysteine residue near the end of the TMD is modified by stearate[77]. The location of the cysteine relative to the TMD was shown to be critical for stearate attachment.…”
Section: Protein Palmitoylationmentioning
confidence: 99%
“…For proteins with multiple palmitoylated cysteines, the heterogeneous fatty acylation pattern is different for each cysteine. For example, the hemagglutinin protein (HA) of influenza virus is S-acylated at three cysteines: two contain only palmitate whereas a cysteine residue near the end of the TMD is modified by stearate[77]. The location of the cysteine relative to the TMD was shown to be critical for stearate attachment.…”
Section: Protein Palmitoylationmentioning
confidence: 99%
“…Another viral S-acylated protein is the hemagglutinin of Influenza virus. S-acylation of its all three cysteine residues by the host cell S-acylation machinery is essential for the replication and infection of the virus (Zurcher et al, 1994; Wagner et al, 2005; Brett et al, 2014). …”
Section: S-acylationmentioning
confidence: 99%
“…Although it has been shown before that overexpressed HA is efficiently and completely acylated even upon introduction of mutations and truncations (Brett et al ., ), we performed radioactive palmitic acid labelling, revealing that Δ1 is indeed palmitoylated as well as the mutant wtC559S and wt, taken as examples, whereas no palmitic acid band is visible for wtC3S mutant (Figure S5; Scolari et al ., ). Furthermore, we analysed the donor–acceptor ratio of our chimeric proteins and found that within different experiments, the relative level of expression of GPImCFP to the respective HA variant did not significantly vary (Fig.…”
Section: Resultsmentioning
confidence: 99%